Adenocalymma calcareum sp nov (Bignoniaceae) from Brazilian Amazonia and a key to the Amazonian species of the genus - Udulutsch, Renata Giassi; de Assis, Marco Antonio [UNESP]; Dias, Pedro (Wiley-Blackwell Publishing, Inc, 2009)
A new species of Adenocalymma (Bignoniaceae, Bignonieae) is described and illustrated. Adenocalymma calcareum Udulutsch & P. Dias sp. nov. is known only from the Rondonia State of western Brazil. Its main diagnostic features are dark yellow corolla provided with nectaries, lepidote ovary, glabrous capsule with prominently thick and calcareous wings and wingless seeds. A discussion on the relationships of the new taxon and a key to all species of Adenocalymma reported from Brazilian Amazonia are provided.